Late Glacial and Holocene lead XRF core scanning data from Füramoos, Southwestern Germany - Kern, Oliver A; Koutsodendris, Andreas; Süfke, Finn; Gutjahr, Marcus; Mächtle, Bertil; Pross, Jörg (PANGAEA, 2021)
Lead content was analyzed by X-ray fluorescence core scanning (XRF-CS) in samples from the Late Glacial and Holocene (c. 14500 – 200 yrs cal. BP) obtained from an ombrotrophic peat bog at Füramoos (southern Germany). The age-depth-model is based on a total of 14 radiocarbon dates and constrained using BACON.
Keywords: Füramoos; Geochemistry; lead; Pb; Peat bog; pollution; Vegetation